2008
DOI: 10.3389/neuro.04.004.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-connectivity and hyper-plasticity in the medial prefrontal cortex in the valproic acid animal model of autism

Abstract: The prefrontal cortex has been extensively implicated in autism to explain defi cits in executive and other higher-order functions related to cognition, language, sociability and emotion. The possible changes at the level of the neuronal microcircuit are however not known. We studied microcircuit alterations in the prefrontal cortex in the valproic acid rat model of autism and found that the layer 5 pyramidal neurons are connected to signifi cantly more neighbouring neurons than in controls. These excitatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 39 publications
12
149
2
5
Order By: Relevance
“…In particular, the numbers of action potentials generated by current steps were lower (Fig. 1C), which confirms a previously reported finding in early postnatal animals (Rinaldi et al, 2008a). This deficit was not caused by a general impairment in the ability of neurons to produce action potentials, since single-spike properties, such as rheobase and spike shape, were unchanged.…”
Section: Development Of Intrinsic Excitabilitysupporting
confidence: 79%
See 3 more Smart Citations
“…In particular, the numbers of action potentials generated by current steps were lower (Fig. 1C), which confirms a previously reported finding in early postnatal animals (Rinaldi et al, 2008a). This deficit was not caused by a general impairment in the ability of neurons to produce action potentials, since single-spike properties, such as rheobase and spike shape, were unchanged.…”
Section: Development Of Intrinsic Excitabilitysupporting
confidence: 79%
“…At a physiological level, previous work has shown that neocortical pyramidal neurons of 2-week-old VPA-exposed animals exhibit two strong abnormalities: impaired intrinsic excitability and excessive NMDA currents (Rinaldi et al, , 2008a. Using whole-cell patch recordings from medial prefrontal cortex (mPFC), we confirmed these findings and went on to trace their postnatal time course.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The existence and structure of brain-specific imprinted-gene network should have important implications for pharmacological interventions; for example, of the 11 genes most-highly altered in expression from treatment of mice with the mood-stabilizer drug valproic acid (Chetcuti et al 2006), two are imprinted (Peg3 and Sfmbt2), one is predicted to be imprinted (Zic1) (Luedi et al 2007), one interacts directly with the imprinted gene Wt1 (Par-4) (Richard et al 2001), and one (Kcna1) interacts directly with Cntnap2 (Strauss et al 2006). Such a striking concentration of imprinted-gene related expression changes is consistent with the molecular function of valproic acid as a histone deacetylase inhibitor, an agent that exhibits differential epigenetic effects on imprinted genes (e. g., Baqir and Smith 2006); moreover, valproic acid during human or rodent pregnancy is a highly-penetrant cause of autism in offspring (Rinaldi et al 2008;Dufour-Rainfray et al 2010), and valproic acid partially restores levels of MeCP2 in a mouse model of Rett syndrome (Vecsler et al 2010). Might such epigenetic treatments exert their effects though canalizing or decanalizing neurological-pathway functions of interacting imprinted genes?…”
Section: An Imprinted-gene Network For Attachment Of the Social Brainmentioning
confidence: 55%